Grinding material slurry and grinding method thereof
By introducing manganese oxide particles, permanganate ions, and phosphoric acid into the abrasive slurry and using surfactants, the problems of dispersibility and cleaning were solved, and efficient SiC substrate abrasion was achieved.
Patent Information
- Application Number
- CN202380047740.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-20
- Publication Date
- 2025-02-07
AI Technical Summary
Existing abrasive slurries containing manganese oxide particles have insufficient dispersion, easily clogging the supply channels and are difficult to clean during the grinding process, affecting the grinding efficiency and quality of SiC substrates.
The abrasive slurry containing manganese oxide particles, permanganate ions and phosphoric acid is used, combined with cellulose-based surfactants and cationic surfactants to improve dispersibility and grinding rate, and the particle size and composition ratio are ensured through specific manufacturing methods.
It achieves high dispersion and high grinding rate, reduces the risk of clogging, simplifies the cleaning process, and improves the grinding efficiency and quality of SiC substrates.
Smart Images

Figure BDA0005192469360000061 
Figure HDA0005192469370000011
Abstract
Description
Technical Field
[0001] The present invention relates to abrasive slurry and a grinding method thereof. Background Art
[0002] In the so-called power devices, semiconductor devices are used to replace the silicon used in the past as substrates by using silicon carbide (SiC), gallium nitride, diamond, etc. to achieve higher voltage resistance and higher current. Since the substrates formed by these materials have a larger band gap than the conventional silicon substrates, they can withstand higher voltages.
[0003] Among them, a substrate formed of silicon carbide (hereinafter referred to as a SiC substrate) is not only excellent in hardness, heat resistance, and scientific stability, but also excellent in terms of cost. On the other hand, since the SiC substrate has a higher hardness than the conventional silicon substrate, an abrasive slurry containing manganese oxide particles as abrasive grains, such as disclosed in Patent Document 1, has been developed as an abrasive slurry used in a polishing process such as a process of finishing the surface of the SiC substrate into a mirror surface in the manufacturing process of the SiC substrate and a polishing process using the so-called CMP (Chemical Mechanical Polishing) method.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-071787 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, most of the abrasive slurries containing manganese oxide particles as abrasive grains disclosed in Patent Document 1 have insufficient dispersibility, and the abrasive slurries are in a viscous liquid state, so the supply pipe for supplying the abrasive slurries is easily blocked. In addition, during the grinding process, since the abrasive slurry adheres to the surface of the SiC substrate as the object to be ground, or on the devices such as the grinding pad used in the grinding, even when the grinding pad or the SiC substrate after the grinding process is washed, the abrasive slurry is difficult to fall off, and the washing process needs to spend time.
[0009] In view of the above problems, the present invention provides an abrasive slurry and a polishing method having excellent dispersibility and showing a high polishing rate.
[0010] Means for solving problems
[0011] The polishing material slurry of the present invention made in order to solve the above-mentioned problems is characterized by comprising manganese oxide abrasive grains containing manganese oxide particles, permanganate ions, and phosphoric acid.
[0012] The polishing slurry of the present invention has excellent dispersibility and exhibits a high polishing rate because it contains manganese oxide abrasive grains including manganese oxide particles, permanganate ions, and phosphoric acid.
[0013] The manganese oxide particles contained in the manganese oxide abrasive grains include manganese (II) oxide (MnO), manganese (III) trioxide (Mn 2 O 3 ), manganese dioxide (IV) (MnO 2 ), manganese (II, III) tetraoxide (Mn 3 O 4 ) etc. It should be noted that the manganese oxide abrasive grains may be abrasive grains formed by mixing one type or two or more types of manganese oxide particles.
[0014] In addition, the manganese oxide abrasive grains may also contain abrasive grains other than the above-mentioned manganese oxide particles within the range that the effect of preventing the warping and cracking caused by the Twyman effect on the object to be polished, such as a SiC substrate, as the abrasive slurry of the present invention, is not damaged. As abrasive grains other than manganese oxide particles, compounds such as oxides, hydroxides, carbides, and other carbon materials of at least one element selected from Mg, B, Si, Ce, Al, Zr, Fe, Ti, and Cr can be listed. Specifically, aluminum oxide, silicon dioxide, cerium oxide, zirconium oxide, titanium oxide, chromium oxide, iron oxide, magnesium hydroxide, cerium hydroxide, silicon carbide, boron carbide, and diamond can be listed. They can also be used in one or in combination of two or more. In addition, the manganese oxide particles can also be composited with abrasive grains other than manganese oxide particles, for example, particles obtained by surface coating of manganese oxide particles by abrasive grains other than manganese oxide particles, or particles obtained by covering the surface of abrasive grains other than manganese oxide particles by manganese oxide particles.
[0015] In addition, if the cumulative volume 50% particle size (D50) of the manganese oxide abrasive grains obtained by laser diffraction / scattering particle size distribution measurement is 0.1 μm or more, it is preferred from the viewpoint of having a high polishing force, and if it is 5.0 μm or less, it is preferred from the viewpoint of suppressing the roughness of the surface of the object to be polished, such as a SiC substrate. Therefore, the cumulative volume 50% particle size (D50) of the manganese oxide abrasive grains obtained by laser diffraction / scattering particle size distribution measurement is more preferably 0.15 μm or more and 4.5 μm or less, and further preferably 0.2 μm or more and 4.0 μm or less.
[0016] Here, the particle size (D50) of the manganese oxide abrasive grains at a cumulative volume of 50% obtained by the laser diffraction / scattering particle size distribution measurement method is prepared by diluting a mixture obtained by bead-crushing the manganese oxide abrasive grains in the method for producing the abrasive slurry of the present invention described later with water so that the concentration of the mixture becomes about 0.01%, and then measuring it using a laser diffraction / scattering particle size distribution measurement device (MicrotracBEL Co., Ltd.: MT3300EXII).
[0017] Furthermore, from the viewpoint of fully improving the grinding rate of high hardness materials such as silicon carbide, ensuring the preferred fluidity of the abrasive in the grinding slurry, and preventing the viewpoint of agglomeration, the content of the manganese oxide abrasive contained in the grinding material slurry of the present invention is preferably 0.5 mass % or more and 20 mass % or less, and more preferably 0.5 mass % or more and 10 mass % or less relative to the total amount of the grinding slurry. In addition, if the content of the manganese oxide particles contained in the manganese oxide abrasive is 1 mass % or more and 5 mass % or less, it is further preferred from the viewpoint of fully improving the grinding rate. It should be noted that in this specification, the content in the grinding material slurry of the present invention is the content in the grinding slurry before the start of grinding unless otherwise specified.
[0018] Furthermore, the polishing material slurry of the present invention contains permanganate ions (MnO 4 - ). The permanganate ions can have a high grinding force on high hardness materials such as silicon carbide by being used in combination with manganese oxide abrasive grains as an oxidant. Here, the supply source of the permanganate ions is preferably permanganate. The permanganate may include alkali metal salts of permanganate or alkaline earth metal salts of permanganate. Furthermore, from the perspective of easy acquisition and improvement of the grinding efficiency of the abrasive slurry of the present invention, the permanganate as the supply source of the permanganate ions is preferably an alkali metal salt of permanganate, and more preferably sodium permanganate or potassium permanganate. It should be noted that these permanganates may be used alone or in combination of two or more.
[0019] In addition, from the viewpoint of fully improving the grinding rate, the content of the permanganate ion in the grinding material slurry of the present invention is preferably 0.5 mass % or more relative to the total amount of the grinding material slurry of the present invention. In addition, from the viewpoint of preventing the crystallization caused by increasing the addition, ensuring the safety of the operation of the grinding material slurry, or even if the addition is increased, the tendency of the grinding rate saturation will occur, etc., the content of the permanganate ion in the grinding material slurry of the present invention is preferably 3.2 mass % or less relative to the total amount of the grinding material slurry of the present invention. That is, the content of the permanganate ion is preferably 0.5 mass % or more and 3.2 mass % or less relative to the total amount of the grinding material slurry of the present invention, more preferably 1.0 mass % or more and 2.1 mass % or less. It should be noted that the content of the permanganate ion is measured by ion chromatography or absorptiometry.
[0020] Furthermore, the polishing material slurry of the present invention contains phosphoric acid in addition to the above-mentioned manganese oxide abrasive and permanganate ions. Phosphoric acid can improve the dispersibility of the polishing material slurry of the present invention by using it together with manganese oxide abrasive and permanganate ions.
[0021] The phosphoric acid contained in the polishing material slurry of the present invention is preferably an inorganic phosphorus compound. Specifically, as the phosphoric acid compound, sodium phosphate (trisodium phosphate (anhydride) (Na 3 PO 4 ), CAS No.: 7601-54-9; Trisodium phosphate 12 hydrate (Na 3 PO 4 12H 2 О), CAS number: 10101-89-0; Sodium dihydrogen phosphate (NaH 2 PO 4 ), CAS number: 7558-80-7; disodium hydrogen phosphate (Na 2 HPO 4 ), CAS No.: 7558-79-4) or potassium phosphate (tripotassium phosphate (anhydride) (K 3 PO 4 ), CAS No.: 7778-53-2; Tripotassium phosphate monohydrate (K 3 PO 4 ·H 2 O), CAS number: 27176-10-9; Potassium hydrogen phosphate trihydrate (K 2 HPO 4 ·H 2 O), CAS number: 16788-57-1; potassium dihydrogen phosphate (KH 2 PO 4 ), CAS number: 7778-77-0; Potassium hydrogen phosphate (K 2 HPO4 ), CAS number: 7758-11-4).
[0022] In addition, examples of metaphosphate compounds include sodium metaphosphate (NaPO 3 ) n , CAS No.: 35270-09-8) or potassium metaphosphate (KPO 3 ) n ,CAS number: 7790-53-6.
[0023] Examples of the hexametaphosphate compound include sodium hexametaphosphate (NaH 7 P 6 O 18 ), CAS number: 10124-56-8.
[0024] Examples of the pyrophosphate compound include sodium pyrophosphate (sodium pyrophosphate (anhydrous) (Na 4 P 2 O 7 ), CAS No.: 7722-88-5; Sodium pyrophosphate decahydrate (Na 4 P 2 O 7 10H 2 О), CAS No.: 13472-36-1; Sodium pyrophosphate (Na 2 H 2 P 2 O 7 ), CAS No.: 7758-16-9) or potassium pyrophosphate (K 4 P 2 O 7 ), CAS number: 7320-34-5.
[0025] Examples of polyphosphate compounds include sodium polyphosphate (Na 3 P 3 O 10 X 2 ), CAS No.: 68915-31-1; Potassium polyphosphate (K 3 P 3 O 10 X 2 ), CAS number: 68956-75-2.
[0026] Examples of tripolyphosphate compounds include sodium tripolyphosphate (Na 5 P 3 O 10 ), CAS number: 7758-29-4 or potassium tripolyphosphate (K 5 P 3 O 10), CAS number: 13845-36-8.
[0027] Furthermore, their salts or hydrates can be listed. In the case of their salts, preferably alkali metal salts or alkaline earth metal salts, particularly more preferably sodium salts or potassium salts. In addition, particularly in the grinding material slurry of the present invention, from the viewpoint of a small amount of effective high dispersibility and the viewpoint of fully improving the grinding rate, more preferably metaphosphate compounds, hexametaphosphate compounds, pyrophosphate compounds (sodium pyrophosphate, potassium pyrophosphate), polyphosphate compounds (sodium polyphosphate or potassium polyphosphate) or tripolyphosphate compounds. It should be noted that these phosphoric acids can also be used one or two or more are mixed and used.
[0028] Furthermore, among the above-mentioned inorganic phosphorus compounds, pyrophosphate compounds are preferred from the viewpoint of high dispersibility and sufficient improvement of polishing rate. Among the pyrophosphate compounds, alkali metal salts of pyrophosphate and alkaline earth metal salts of pyrophosphate are more preferred, and sodium pyrophosphate or potassium pyrophosphate is particularly preferred.
[0029] In addition, from the viewpoint of dispersibility, the content of phosphoric acid in the grinding material slurry of the present invention is preferably 0.01% by mass or more relative to the total amount of the grinding material slurry of the present invention. In addition, from the aspect that the tendency of saturation of the grinding rate will occur even if the addition amount is increased, the content of phosphoric acid in the grinding material slurry of the present invention is preferably 0.1% by mass or less relative to the total amount of the grinding material slurry of the present invention. That is, the content of phosphoric acid is preferably 0.01% by mass or more and 0.1% by mass or less relative to the total amount of the grinding material slurry of the present invention, and is more preferably 0.02% by mass or more from the viewpoint of improving dispersibility, and is more preferably 0.05% by mass or less from the viewpoint of fully improving the grinding rate. It should be noted that in this specification, the content of phosphoric acid is the total amount of the compound classified as phosphoric acid as long as there is no special description.
[0030] Furthermore, when the content of phosphoric acid in the abrasive slurry of the present invention is expressed as a mass ratio relative to the content of manganese oxide abrasive grains in the abrasive slurry of the present invention, it is preferably 0.5% or more and 5.0% or less, more preferably 0.8% or more and 3.0% or less, and even more preferably 1.0% or more and 2.0% or less.
[0031] Furthermore, the polishing material slurry of the present invention is characterized by further containing a cellulose-based surfactant and / or a cationic surfactant.
[0032] The polishing slurry of the present invention can improve low friction properties by further containing a cellulose-based surfactant and / or a cationic surfactant.
[0033] As cellulose-based surfactants, any of anionic surfactants, cationic surfactants, and nonionic surfactants are known. First, anionic surfactants include those obtained by introducing negative groups, such as carboxyl groups, alkoxy groups, and hydroxyl groups, into the skeleton of cellulose. In addition, cationic surfactants include cationized cellulose. Furthermore, nonionic groups include alkyl celluloses such as ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, and hydroxypropyl methyl cellulose.
[0034] Among these cellulose-based surfactants, anionic surfactants are preferred, and surfactants containing carboxyl groups are particularly preferred. Carboxymethyl cellulose and its derivatives are preferred from the viewpoint of low friction. Carboxymethyl cellulose is a compound in which a carboxymethyl group is bonded to a part of the hydroxyl group of the pyranose glucose monomer constituting the cellulose skeleton. In addition, carboxymethyl cellulose derivatives include alkali metal salts of carboxymethyl cellulose, specifically salts such as sodium salts or potassium salts. Furthermore, carboxymethyl cellulose derivatives include compounds in which hydroxyl groups, alkyl groups, etc. are bonded to the side chains thereof within the range of not losing the surface activity of the carboxymethyl cellulose. In addition, cellulose-based surfactants include crystalline cellulose and its modified products (e.g., Avicel manufactured by Asahi Kasei Corporation). It should be noted that these cellulose-based surfactants can also be used alone or in a mixture of two or more.
[0035] Examples of the cationic surfactant include amine salt-type surfactants and quaternary ammonium salt-type surfactants, and are preferably surfactants having a quaternary ammonium ion moiety. Examples of the cationic surfactant having a quaternary ammonium ion moiety include salts represented by the following general formula (1).
[0036] [Chemical formula 1]
[0037]
[0038] (In the above general formula (1), R 1 , R 2 , R 3 and R 4 are independently alkyl, aryl or arylalkyl, or R 1 , R 2 and R 3 Bonded to form a pyridine ring, R 4 is alkyl, aryl or arylalkyl, X - It is a monovalent anion.)
[0039] In the above general formula (1), R 1 , R 2 , R 3 and R 4The alkyl group represented is preferably an alkyl group having 1 to 20 carbon atoms, and specifically, methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, pentyl, isopentyl, tert-pentyl, hexyl, heptyl, isoheptyl, tert-heptyl, n-octyl, isooctyl, 2-ethylhexyl, tert-octyl, nonyl, isononyl, decyl, isodecyl, undecyl, dodecyl, tridecyl, isotridecyl, tetradecyl, hexadecyl, octadecyl, eicosyl, etc. are listed, and a straight-chain alkyl group is preferred. 1 , R 2 , R 3 and R 4 The aryl group represented by is preferably phenyl. 1 , R 2 , R 3 and R 4 The arylalkyl represented by is preferably benzyl, phenethyl, etc. - The monovalent anion represented by is preferably a halide ion. The halide ion is preferably a chloride ion or a bromide ion. 1 , R 2 , R 3 and R 4 The aromatic ring and R in the aryl group or arylalkyl group represented by 1 , R 2 and R 3 The bonded pyridine ring may be substituted by an alkyl group or an amino group, and the methylene group in the arylalkyl group may be substituted by -O-. 1 , R 2 and R 3 The bonded pyridine ring can also be condensed with a benzene ring.
[0040] Examples of the cationic surfactant represented by the general formula (1) include distearyl dimethyl ammonium chloride (shown in the structural formula C 18 H 37 N + C 18 H 37 (CH 3 ) 2 ·Cl - ), benzalkonium chloride (shown as formula C 6 H 5 CH 2 N + (CH 3 ) 2 RCl - (R=C 8 H 17 ~C 18 H 37 , long chain alkyl)), benzethonium chloride (molecular formula C 27 H 42 ClNO2 ), cetylpyridinium chloride (molecular formula C 21 H 38 NCl), hexadecyltrimethylammonium bromide (shown in the structural formula (C 16 H 33 )N + (CH 3 ) 3 Br - ), dequalinium chloride (molecular formula C 30 H 40 C l2 N 4 )wait.
[0041] In addition, from the viewpoint of improving low friction, the total content of the cellulose surfactant and / or cationic surfactant in the grinding material slurry of the present invention is preferably 0.1% by mass or more relative to the total amount of the grinding material slurry of the present invention. In addition, from the viewpoint of fully improving the grinding rate, the total content of the cellulose surfactant and / or cationic surfactant in the grinding material slurry of the present invention is preferably 1% by mass or less relative to the total amount of the grinding material slurry of the present invention. That is, the total content of the cellulose surfactant and / or cationic surfactant is preferably 0.1% by mass or more and 1% by mass or less relative to the total amount of the grinding material slurry of the present invention, more preferably 0.1% by mass or more and 0.5% by mass or less. It should be noted that in this specification, the total content of the cellulose surfactant and / or cationic surfactant is its content in the case of containing only any one of the cellulose surfactant and / or cationic surfactant, and is their total amount in the case of containing both.
[0042] In addition, the polishing material slurry of the present invention is characterized in that the content of the above-mentioned manganese oxide abrasive is greater than 0.5 mass% and less than 20 mass%, the content of the above-mentioned permanganate ion is greater than 0.5 mass% and less than 3.2 mass%, and the content of the above-mentioned phosphoric acid is greater than 0.01 mass% and less than 0.1 mass%.
[0043] As described above, in the polishing material slurry of the present invention, if the content of the above-mentioned manganese oxide abrasive is greater than 0.5 mass% and less than 20 mass%, the content of the above-mentioned permanganate ions is greater than 0.5 mass% and less than 3.2 mass%, and the content of the above-mentioned phosphoric acid is greater than 0.01 mass% and less than 0.1 mass%, it is preferred in terms of excellent dispersibility and showing a high polishing rate.
[0044] In addition, the grinding material slurry of the present invention is characterized in that the content of the above-mentioned manganese oxide abrasive is greater than 0.5 mass% and less than 20 mass%, the content of the above-mentioned permanganate ions is greater than 0.5 mass% and less than 3.2 mass%, the content of the above-mentioned phosphoric acid is greater than 0.01 mass% and less than 0.1 mass%, and the total content of the above-mentioned cellulose-based surfactant and / or the above-mentioned cationic surfactant is less than 1.0 mass%.
[0045] As described above, in the polishing material slurry of the present invention, if the content of the above-mentioned manganese oxide abrasive is greater than 0.5 mass% and less than 20 mass%, the content of the above-mentioned permanganate ion is greater than 0.5 mass% and less than 3.2 mass%, the content of the above-mentioned phosphoric acid is greater than 0.01 mass% and less than 0.1 mass%, and the total content of the above-mentioned cellulose-based surfactant and / or the above-mentioned cationic surfactant is less than 1.0 mass%, then in addition to excellent dispersibility and showing a high polishing rate, it is preferred from the viewpoint of excellent low friction.
[0046] Here, the grinding material slurry of the present invention contains a dispersion medium for dissolving or dispersing the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acid and cellulose surfactants and / or cationic surfactants. If the dispersion medium is a water-soluble organic solvent such as water, alcohol, ketone or a mixture thereof, it is preferred in terms of fully improving the polishing rate, and water is more preferred. The content of the dispersion medium is preferably 60% by mass or more and 99.9% by mass or less relative to the total amount of the grinding material slurry, and more preferably 80% by mass or more and 90% by mass or less.
[0047] Furthermore, the grinding material slurry of the present invention may also contain any additives other than the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acid, cellulose-based surfactants and / or cationic surfactants and dispersion medium. Among them, the arbitrary additives are dispersants, pH adjusters, viscosity adjusters, chelating agents and rust inhibitors, etc. The content of the arbitrary additives is preferably 40% by mass or less, more preferably 20% by mass or less, and further preferably 10% by mass or less relative to the total amount of the grinding material slurry of the present invention.
[0048] It should be noted that the abrasive slurry of the present invention can be set in a form in which the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acid, cellulose-based surfactants and / or cationic surfactants, dispersion media and any additives are appropriately mixed, for example, it can also be set in a set of preparations in which these constituent components are divided into two or more kinds. The composition of the set can be any form as long as the grinding ability can be fully exerted when adjusting the abrasive slurry.
[0049] A polishing method for polishing an object to be polished using the above-mentioned abrasive slurry of the present invention will be described below.
[0050] The following polishing methods can be listed: supplying the abrasive slurry of the present invention to a polishing pad, making the polished surface of the object to be polished contact with the polishing pad, and polishing by relative movement between the two. Here, it can also be a method of allowing the abrasive slurry of the present invention to flow freely, or a method of circulating the abrasive slurry of the present invention by repeatedly performing the following operations: recovering the abrasive slurry of the present invention supplied to the polishing pad for polishing, and supplying the recovered abrasive slurry of the present invention to the polishing pad again. Since the abrasive slurry of the present invention can be circulated repeatedly to polish the object to be polished, the usage amount can be suppressed. Here, the polishing pad can use, for example, non-woven fabrics that have been used so far, or pads impregnated with resins such as polyurethane or epoxy, and suede materials. If the polishing pressure is 0.5×10 4 Pa or more and 1.0×10 5 Pa or less, especially 1.0×10 4 Pa or more and 5.0×10 4 Pa or less is preferred from the perspectives of polishing force and ease of operation of the polishing jig. The supply rate of the polishing material slurry is preferably 10 mL / min to 500 mL / min, more preferably 50 mL / min to 250 mL / min.
[0051] The object to be ground by the abrasive slurry of the present invention is, for example, a high-hardness material with a Mohs hardness of 8 or more. Here, the Mohs hardness is a result of a method of applying scars to a standard material and digitizing the hardness, and can be measured by a Mohs hardness meter by a conventional method. The Mohs hardness specifies standard materials ranging from 1 to 10 in order from softness, and the specific standard materials are: Mohs hardness 1 is talc, 2 is gypsum, 3 is calcite, 4 is fluorite, 5 is apatite, 6 is orthoclase, 7 is quartz, 8 is topaz, 9 is corundum, and 10 is diamond. Mohs hardness is a high-hardness material with a hardness of 8 or more on the Mohs hardness meter, for example, silicon carbide (Mohs hardness of about 9), gallium nitride (Mohs hardness of about 9), diamond, etc.
[0052] Moreover, the abrasive slurry of the present invention can be used for the CMP (Chemical Mechanical Polishing) process after the polishing of the substrate formed by the high hardness material. In particular, the abrasive slurry of the present invention can be used for the polishing of the substrate formed by silicon carbide (SiC), that is, the SiC substrate, which can fully improve the polishing rate and effectively prevent the warping and cracking caused by the Terwyman effect. SiC substrates usually use single-crystal silicon carbide substrates. As a result, as its crystal system, hexagonal crystals or rhombohedral crystals can usually be listed. From the perspective of the effect of the abrasive slurry that can prevent the warping and cracking caused by the Terwyman effect, hexagonal crystals are preferred. The polymorphs of hexagonal crystals are 2H, 4H, 6H, 8H, and 10H. The polymorphs of rhombohedral crystals are 15R.
[0053] Next, the method for producing the abrasive slurry of the present invention described above will be described below.
[0054] First, pure water, manganese dioxide (abrasive particles, MnO 2 ), phosphoric acid (e.g. sodium salt of pyrophosphate), beads (made of zirconium oxide, φ0.4 mm), the container is placed on a paint shaker (60 Hz), and the container is rotated at high speed to mix manganese dioxide (abrasive grains, MnO 2 ) mixed and crushed.
[0055] The mixed and pulverized manganese dioxide (abrasive particles, MnO 2 ) is separated from the beads using a centrifugal separator (himac CT 6E manufactured by Hitachi Koki Co., Ltd.), and the supernatant is collected.
[0056] The solid content concentration in the collected supernatant, i.e., the manganese oxide abrasive grain concentration, is measured by a heated moisture meter, and pure water is added in such a manner as to obtain a predetermined concentration to obtain an abrasive slurry intermediate. It should be noted that a cellulose-based surfactant and / or a cationic surfactant may also be added to the obtained abrasive slurry intermediate.
[0057] Then, the abrasive slurry intermediate is mixed with potassium permanganate (KMnO 4 ) are mixed to obtain the abrasive slurry of the present invention.
[0058] It should be noted that, in the present specification, when “X to Y” (X, Y are arbitrary numbers) is expressed, unless otherwise specified, it includes the meaning of “X or more and Y or less”, and also includes the meaning of “preferably greater than X” or “preferably less than Y”. In addition, when it is expressed as “X or more” (X is an arbitrary number) or “Y or less” (Y is an arbitrary number), it also includes the intention of “preferably greater than X” or “preferably less than Y”.
[0059] Effects of the Invention
[0060] The polishing material slurry of the present invention has excellent dispersibility and can sufficiently increase the polishing rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a table showing the physical property values and measurement results of the polishing material slurries of Examples 1 to 10 and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0062] Hereinafter, the polishing material slurry according to the embodiment of the present invention will be further described by the following examples. However, the following examples do not limit the present invention.
[0063] (Example 1)
[0064] Pure water, manganese dioxide (MnO 2 ), sodium pyrophosphate as a phosphoric acid (specifically, sodium pyrophosphate 10 hydrate (Na 4 P 2 O 7 10H 2 O), CAS number: 13472-36-1), beads (zirconia φ 0.4 mm), the container is placed on a paint shaker (60 Hz), the container is rotated at high speed, and manganese dioxide is mixed and crushed. The contents of these components are prepared in such a way that the content of manganese dioxide becomes 30% by mass and the content of sodium pyrophosphate becomes 0.3% by mass relative to the total amount of the abrasive slurry of Example 1.
[0065] The mixture containing the mixed and pulverized manganese dioxide in the container is separated from the beads using a centrifugal separator (himac CT 6E manufactured by Hitachi Koki Co., Ltd.) or the like, and the supernatant is collected. It should be noted that the supernatant obtained in this step becomes a measurement sample before the addition of potassium permanganate in the dispersibility test described later.
[0066] The solid content concentration in the collected supernatant, that is, the manganese oxide abrasive concentration, was measured with a heated moisture meter, and pure water was added so as to achieve a predetermined concentration, thereby obtaining an abrasive slurry intermediate.
[0067] Then, the abrasive slurry intermediate was mixed with KMnO 4 Potassium permanganate (KMnO) with a mass% concentration of 3.2 mass% 4) aqueous solution to obtain the abrasive slurry of Example 1. The content of permanganate ions is prepared in such a way that it becomes 1.2% by mass relative to the total amount of the abrasive slurry of Example 1. In addition, the mass ratio of the total content of phosphoric acid in Example 1 to the content of manganese oxide abrasive is 1.0%. It should be noted that the abrasive slurry of Example 1 obtained in this process becomes the measurement sample after the addition of potassium permanganate in the dispersibility test described later. In addition, Figure 1 The composition of the abrasive slurry shown in is the composition of the final product.
[0068] (Example 2)
[0069] In Example 2, the same manufacturing method as in Example 1 was carried out except that the sodium pyrophosphate used in Example 1 was replaced with trisodium phosphate to be 0.3% by mass relative to the total amount of the abrasive slurry of Example 2, thereby obtaining the abrasive slurry of Example 2. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Example 2 was 1.0%.
[0070] (Example 3)
[0071] In Example 3, in addition to the components used in Example 1, the abrasive slurry intermediate of Example 1 and potassium permanganate (KMnO 4 ) was added to the abrasive slurry intermediate of Example 1 as a cellulose-based surfactant and mixed in a manner of 0.25% by mass relative to the total amount of the abrasive slurry of Example 3. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry of Example 3. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Example 3 was 1.0%.
[0072] (Example 4)
[0073] In Example 4, manganese dioxide (MnO 2 ) was prepared in such a way that the content of the abrasive slurry was 0.5% by mass relative to the total amount of the abrasive slurry of Example 4. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry of Example 4. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Example 4 was 4.0%.
[0074] (Example 5)
[0075] In Example 5, manganese dioxide (MnO 2) was prepared in such a way that the content of the abrasive slurry was 20% by mass relative to the total amount of the abrasive slurry of Example 5. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry of Example 5. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Example 5 was 0.1%.
[0076] (Example 6)
[0077] In Example 6, the abrasive slurry intermediate and KMnO 4 Potassium permanganate (KMnO) with a mass% concentration of 5.6 mass% 4 ) aqueous solution, and the content of permanganate ions was prepared in a manner that was 3.2% by mass relative to the total amount of the abrasive slurry of Example 6. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry of Example 6. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Example 6 was 1.0%.
[0078] (Example 7)
[0079] In Example 7, the same manufacturing method as in Example 1 was carried out except that the content of sodium pyrophosphate was prepared to be 0.01 mass % relative to the total amount of the abrasive slurry of Example 7, thereby obtaining the abrasive slurry of Example 7. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Example 7 was 0.5%.
[0080] (Example 8)
[0081] In Example 8, the same manufacturing method as in Example 1 was carried out except that the content of sodium pyrophosphate was prepared to be 0.1% by mass relative to the total amount of the abrasive slurry of Example 8, thereby obtaining the abrasive slurry of Example 8. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Example 8 was 5.0%.
[0082] (Example 9)
[0083] In Example 9, the content of sodium pyrophosphate was 0.018 mass % relative to the total amount of the polishing material slurry of Example 9, and other phosphoric acids (specifically, tripotassium phosphate (anhydride) (K 3 PO 4 ), CAS number: 7778-53-2, sodium metaphosphate (NaPO 3 ) n 、CAS No.: 35270-09-8、Potassium pyrophosphate (K 4 P 2 O 7), CAS No.: 7320-34-5, sodium polyphosphate (Na 3 P 3 O 10 X 2 ), CAS No.: 68915-31-1 and sodium tripolyphosphate (Na 5 P 3 O 10 ), CAS No.: 7758-29-4, and each mixed in equal amounts) was prepared in such a way that the total amount of phosphoric acid was 0.002 mass % (the total amount of phosphoric acid was 0.02 mass %), and the same manufacturing method as in Example 1 was implemented to obtain the abrasive slurry of Example 9. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Example 9 was 1.0%.
[0084] (Example 10)
[0085] In Example 10, the abrasive slurry intermediate of Example 1 and potassium permanganate (KMnO 4 ) was added to the abrasive slurry intermediate of Example 1 and mixed with carboxymethyl cellulose as a cellulose-based surfactant in a manner of 0.1% by mass relative to the total amount of the abrasive slurry of Example 10. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry of Example 10. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Example 10 was 1.0%.
[0086] (Comparative Example 1)
[0087] Comparative Example 1 The same manufacturing method as in Example 1 was carried out except that no phosphoric acid was added to obtain the abrasive slurry of Comparative Example 1. The mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Comparative Example 1 was 0.0%.
[0088] (Comparative Example 2)
[0089] In Comparative Example 2, manganese dioxide (MnO 2 ), according to silicon dioxide (SiO 2 ) was prepared in such a way that the total amount of the abrasive slurry was 2.0 mass % relative to that of Comparative Example 2, and potassium permanganate (KMnO 4 ), except for the above, the same manufacturing method as in Example 1 was implemented to obtain the abrasive slurry of Comparative Example 2. It should be noted that the mass ratio of the total content of phosphoric acid to the content of silicon oxide abrasive in Comparative Example 2 was 1.0%.
[0090] (Comparative Example 3)
[0091] In Comparative Example 3, the abrasive slurry intermediate and KMnO 4 Potassium permanganate (KMnO) with a mass% concentration of 5.6 mass% 4 ) aqueous solution, and the content of permanganate ions was prepared in a manner that was 4% by mass relative to the total amount of the abrasive slurry of Comparative Example 3. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry of Comparative Example 3. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Comparative Example 3 was 1.0%.
[0092] (Comparative Example 4)
[0093] In Comparative Example 4, the same manufacturing method as in Example 1 was carried out except that the content of sodium pyrophosphate was prepared to be 0.001 mass % relative to the total amount of the abrasive slurry of Comparative Example 4, thereby obtaining the abrasive slurry of Comparative Example 4. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Comparative Example 4 was 0.05%.
[0094] (Comparative Example 5)
[0095] In Comparative Example 5, the same manufacturing method as in Example 1 was carried out except that the content of sodium pyrophosphate was prepared to be 0.5 mass % relative to the total amount of the abrasive slurry of Comparative Example 5, thereby obtaining the abrasive slurry of Comparative Example 5. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive in Comparative Example 5 was 25%.
[0096] Then, the following physical property values were measured for the polishing material slurries of Examples 1 to 10 and Comparative Examples 1 to 5. The measured physical property values and the measuring methods of the physical property values are shown below, and the measurement results are shown in Figure 1 middle.
[0097] <Particle size evaluation>
[0098] The samples for measurement were prepared by diluting the mixture containing the abrasive grains mixed and pulverized in a paint shaker in the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 to 5 with water so that the concentration of the mixture became about 0.01%. Then, the particle size (D50) at the cumulative fraction of 50% based on volume was measured using a laser diffraction / scattering particle size distribution measuring apparatus (MT3300EXII manufactured by MicrotracBEL Co., Ltd.).
[0099] <Dispersibility Evaluation>
[0100] The dispersibility of the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 and 3 to 5 was evaluated before and after the addition of potassium permanganate, which is a source of permanganate ions.
[0101] First, the dispersibility before the addition of potassium permanganate is evaluated as follows. The mixture of abrasive particles mixed and crushed in a paint shaker in the grinding material slurry of Examples 1 to 10 and Comparative Examples 1, 3 to 5 is diluted with water in a manner such that the concentration of the mixture becomes about 0.01 mass %, and a sample for measurement is prepared. Then, a particle size (D50) at a cumulative fraction of 50% on a volume basis is measured using a laser diffraction / scattering particle size distribution measuring device (MicrotracBEL Co., Ltd.: MT3300EXII), and if D50 is less than 0.6 μm, it is evaluated as "O (Good)", and if D50 exceeds 0.6 μm, it is evaluated as "× (Bad)".
[0102] Next, the dispersibility after the addition of potassium permanganate was evaluated as follows. The samples for measurement were prepared by diluting the abrasive slurry of Examples 1 to 10 and Comparative Examples 1, 3 to 5 with water in such a manner that the concentration was about 0.01% by mass. Then, a laser diffraction / scattering particle size distribution measuring apparatus (MT3300EXII manufactured by MicrotracBEL Co., Ltd.) was used to measure the particle size (D50) of the cumulative fraction of 50% on a volume basis. If D50 was less than 0.6 μm, it was evaluated as "0 (Good)", and if D50 exceeded 0.6 μm, it was evaluated as "× (Bad)". It should be noted that the abrasive slurry of Comparative Example 2 did not have potassium permanganate (KMnO added) in its abrasive slurry intermediate. 4 ), so the above-mentioned dispersibility evaluation was not performed.
[0103] <Adhesion Evaluation>
[0104] The adhesion of the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 to 5 was determined by visually recognizing the adhesion of each abrasive slurry on a container (wide-mouthed bottle IBOY 250ml manufactured by AS ONE) containing the sample used in the dispersibility evaluation after the addition of potassium permanganate as described above by the tester, and the judgment was made as follows. When the container containing the sample was turned over, if the sample did not adhere to the container, it was evaluated as "00 (Very Good)", if the sample only adhered to the bottom of the container, it was evaluated as "0 (Good)", and if the sample adhered to the bottom and side of the container, or adhered to the side, it was evaluated as "× (Bad)". It should be noted that for the abrasive slurry of Comparative Example 2, potassium permanganate (KMnO) was not added to the abrasive slurry intermediate. 4 ) was used as the sample.
[0105] <Grinding test>
[0106] The polishing rates of the abrasive slurries of Examples 1 to 10 and Comparative Examples 1 to 5 were evaluated by the following steps. A 4H-SiC substrate having a diameter of 4 inches and a deviation angle of 4° after CMP processing was used as the polishing object. The polishing test was performed on the Si surface of the substrate. A single-sided grinder BC-15 manufactured by MAT was used as the polishing device. An IC1000 manufactured by NITTADuPont was used as the polishing pad mounted on the platform. The rotation speed of the platform was set to 60 rpm, and the peripheral speed was set to 7,136 cm / min. In addition, the carrier rotation speed was set to 60 rpm, and the peripheral speed was set to 961 cm / min. Furthermore, the load during polishing was set to 2.8 psi (approximately 1.96×10 4 The polishing rate was calculated from the difference in mass of the substrate before and after polishing. If the polishing rate was 0.10 μm / h or more, it was evaluated as "O (Good)", and if the polishing rate was less than 0.10 μm / h, it was evaluated as "× (Bad)".
[0107] <Crystallization Test>
[0108] Prepare each sample of the abrasive slurry of Examples 1 to 10 and Comparative Examples 1 to 5. Store each prepared sample in a refrigerator set at 10°C for 24 hours. Afterwards, take each sample out of the refrigerator, and use a heating moisture meter to calculate the solid content concentration in each sample, that is, the total value of the manganese oxide abrasive concentration and the potassium permanganate concentration. Moreover, if the solid content concentration after storage is more than 90% of the maintenance rate of the solid content concentration before storage, it is evaluated as "0 (Good)", and if the solid content concentration after storage is lower than 90% of the maintenance rate of the solid content concentration before storage, it is evaluated as "× (Bad)".
[0109] <Friction Characteristics Evaluation>
[0110] The friction characteristics of the abrasive slurry of Examples 1, 3 and 10 are evaluated as follows. A grinding pad (IC1000 made by NITTADuPont) is attached and fixed on the platform of the grinder, and the supply amount of 1L of the abrasive slurry of Examples 1, 3 and 102 is set to 200mL / min, which is supplied to the grinding pad in a cyclic manner. In addition, the workpiece as the object to be ground is placed on the grinding pad. Then, under the state of hanging a spring balance on the workpiece, the platform of the grinder is rotated, and the workpiece and the platform are rotated in the same direction by a forced drive unit. Here, the forced drive unit is provided with a rotating roller that can abut against the workpiece, and the workpiece is rotated by rotating the rotating roller. Then, the spring balance is stretched in the direction in which the workpiece is separated from the forced drive unit, and the forced drive unit leaves the rotating roller from the workpiece and makes the rotation of the workpiece stationary. The digital display value (i.e., tensile force) displayed on the spring balance after the rotation of the workpiece is stationary for 30 seconds is measured. The tensile force measured in this way was divided by the load of the workpiece to obtain the friction coefficient of the abrasive slurry of Examples 1, 3 and 10. If the friction coefficient was 0.35 or less, it was evaluated as "○○ (Very Good)", if the friction coefficient exceeded 0.35 and was 0.38 or less, it was evaluated as "○ (Good)", and if the friction coefficient exceeded 0.38, it was evaluated as "× (Bad)".
[0111] like Figure 1 As shown in , the abrasive slurries of Examples 1 to 10 have excellent dispersibility because the volume-based cumulative fraction of 50% in the particle size distribution obtained by laser diffraction / scattering method before and after the addition of potassium permanganate, a source of permanganate ions, is less than 0.6 μm (D50).
[0112] Regarding the abrasive slurries of Examples 1, 3 to 6, and 8 to 10, the adhesion state of the abrasive slurries on the container containing the sample was checked when the container was turned over. As a result, the sample did not adhere to the container, and the adhesion was very good. In addition, regarding the abrasive slurries of Examples 2 and 7, the sample adhered only to the bottom of the container, and the adhesion was good.
[0113] The polishing rate of the polishing material slurry of Examples 1 to 10 was 0.10 μm / h or more, and thus showed a high polishing rate.
[0114] Since the solid content concentration of the abrasive slurries of Examples 1 to 10 after being stored in a refrigerator set at 10° C. for 24 hours maintained 90% or more of the solid content concentration before storage, it was found that crystals were not precipitated.
[0115] The abrasive slurries of Examples 1, 3, and 10 have a friction coefficient of 0.38 or less, and thus achieve low friction.
[0116] The invention disclosed in this specification includes, in addition to the configurations of each invention or embodiment, configurations specified by changing these partial configurations to other configurations disclosed in this specification within the applicable scope, configurations specified by adding other configurations disclosed in this specification to these configurations, or configurations specified by deleting these partial configurations to the extent that partial effects can be obtained.
[0117] Industrial Applicability
[0118] The abrasive slurry of the present invention has excellent dispersibility and shows a high polishing rate, and is suitable as an abrasive for an object to be polished formed of a high hardness material. In addition, the abrasive slurry of the present invention has excellent dispersibility, so it is easy to wash the SiC substrate or polishing pad as the object to be polished, the viewpoint of suppressing the use amount of washing water, the viewpoint of shortening the washing time, and the viewpoint of reducing the amount of wastewater treatment, which can bring about a reduction in environmental load. Furthermore, the abrasive slurry of the present invention can shorten the polishing process time because it shows a high polishing rate.
Claims
1. An abrasive slurry, characterized in that: It has: Manganese oxide abrasive grains containing manganese oxide particles, Permanganate ions, and Phosphoric acid.
2. The abrasive slurry according to claim 1, characterized in that: The phosphoric acid is an inorganic phosphorus compound.
3. The abrasive slurry according to claim 2, characterized in that: The inorganic phosphorus compound is a pyrophosphate compound.
4. The abrasive slurry according to claim 1, characterized in that: It further contains a cellulose-based surfactant and / or a cationic surfactant.
5. The abrasive slurry according to claim 4, characterized in that: The cellulose-based surfactant contains carboxymethyl cellulose.
6. The abrasive slurry according to any one of claims 1 to 3, characterized in that The content of the manganese oxide abrasive grains is 0.5 mass % or more and 20 mass % or less, The content of the permanganate ion is 0.5 mass % or more and 3.2 mass % or less, The content of the phosphoric acid is 0.01 mass % or more and 0.1 mass % or less.
7. The abrasive slurry according to claim 4 or 5, characterized in that: The content of the manganese oxide abrasive grains is 0.5 mass % or more and 20 mass % or less, The content of the permanganate ion is 0.5 mass % or more and 3.2 mass % or less, The content of the phosphoric acid is 0.01 mass % or more and 0.1 mass % or less, The total content of the cellulose-based surfactant and / or the cationic surfactant is 1.0% by mass or less.
8. A grinding method, characterized in that: It includes: An object to be polished is polished using the abrasive slurry according to any one of claims 1 to 5.
9. A grinding method, characterized in that: It includes: An object to be polished is polished using the abrasive slurry according to claim 6.
10. A grinding method, characterized in that: It includes: An object to be polished is polished using the abrasive slurry according to claim 7.
Citation Information
Patent Citations
Polishing material slurry and polishing method
JP2017071787A